Beyond policy implementation: strengthening capacity building for village sustainable development goals (SDGs) implementation in Cirarab Village - Nural Achmad Raainaa; Kiky Andriyani Dwi Pangestuti; Farda Aisyah Devintasari; Youngki Alfian Dinata; Gabiela Gumilang; Sylvia Rijha Putri; Yoga Pratama; Muhammad Barra Marelangga (PT WIM Solusi Prima, 2026)
The implementation of the Village Sustainable Development Goals (SDGs) is part of the government's efforts to realize sustainable village development through data-based planning and community participation. However, the implementation of the Village SDGs in various regions still faces various obstacles, including in Cirarab Village, Legok District, Tangerang Regency. This study aims to describe the implementation of the Village SDGs, identify the obstacles faced, and analyze efforts to improve the implementation of the Village SDGs in Cirarab Village. The study used a qualitative descriptive approach with a case study design. Data were collected through observation, interviews, documentation, and focus group discussions (FGDs) with informants selected by purposive sampling, including the village head, village officials, PKK cadres, and other related parties. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Village SDGs in Cirarab Village has not been running optimally. The main obstacles include limited outreach regarding the Village SDGs, low human resource capacity in managing SDG applications, the lack of knowledge transfer after the change of SDGs administrator, and suboptimal institutional structures and data management systems. Based on analysis using George C. Edward III's policy implementation theory, the success of Village SDGs implementation is influenced by four factors: communication, resources, implementer disposition, and bureaucratic structure. Outreach and mentoring activities have increased village officials' understanding of the Village SDGs and resulted in recommendations for strengthening the SDGs Working Group (Pokja SDGs) institution, digitizing data management, increasing apparatus capacity, and providing ongoing mentoring. These efforts are expected to increase the effectiveness of Village SDGs implementation as a basis for participatory, data-driven, and sustainable village development.